2019
DOI: 10.1108/lm-06-2019-0037
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the reading habit and attitudes among the rural community in low literacy rate areas in Malaysia

Abstract: Purpose The purpose of this paper is to investigate the reading habit and attitude among rural communities in the low literacy rate areas in Malaysia. Design/methodology/approach Multi-stage cluster and simple random sampling were employed and 400 respondents who live nearby the rural library were selected. Findings Moderate levels of reading attitude were obtained from the result of the study, in which several variables produced a significant relationship in the reading attitude (education level, househol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
23
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 21 publications
(30 reference statements)
5
23
1
2
Order By: Relevance
“…Beberapa waktu yang lalu, The World's Most Literate Nations (WMLN) merilis daftar peringkat negara-negara berwawasan literasi. Penelitian yang dilakukan oleh Jhon W. Miller (Presiden Central Connecticut State University, New britain) ini dilakukan terhadap 61 negara di dunia (Samsuddin, Shaffril, Bolong, & Mohamed, 2019). Dan hasilnya adalah, negara kita berada pada peringkat kedua.…”
Section: Pendahuluanunclassified
“…Beberapa waktu yang lalu, The World's Most Literate Nations (WMLN) merilis daftar peringkat negara-negara berwawasan literasi. Penelitian yang dilakukan oleh Jhon W. Miller (Presiden Central Connecticut State University, New britain) ini dilakukan terhadap 61 negara di dunia (Samsuddin, Shaffril, Bolong, & Mohamed, 2019). Dan hasilnya adalah, negara kita berada pada peringkat kedua.…”
Section: Pendahuluanunclassified
“…Its existence is urgent in human life. Strand & Britz (2018) 14 and Edwards (2018) 15 revealed that the libraries serve as a means of increasing access to information while alleviating community poverty 16,17 . The achievement of access to information and economic progress can be carried out through technological development and supporting cultural changes 9 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Mehra, Singh, Hollenbach, and Partee II (2017) 18 , libraries among rural communities must become centres of information developed by technological means because libraries as agents of change can bring people to a better future. These roles can be conducted if the culture of communities is based on reading and educational interests as formal responsibilities of the library 16,17 . Education will further enhance the roles of libraries concerning their social function as a community space beside its efforts to build community capacity through social inclusion and social capital, which ends in social harmony 19 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the US, community newspapers that are mostly published on a weekly basis account for 62percent of the overall print circulation (Reader, 2018). Print newspapers continue to be read particularly in certain rural areas in countries such as India (Kaushik, 2018;Ramakrishnan, 2017), Africa (Amadu, Mohammed, Alhassan, & Mohammed, 2018;Cilliers, & Bloch, 2018), and Malaysia (Samsuddin, Shaffril, Bolong, & Mohamed, 2020;Zahari, Ariffin, Asmawi, & Ibrahim, 2018). These trends suggest that print newspapers are still regarded as an important form of media communication.…”
Section: Conventional Mediamentioning
confidence: 99%